Ramadan and Eid al-Fitr: Population movement, mass gathering and escalating of COVID-19 – A perspective from Indonesia - Dian Sidik Arsyad; Firzan Nainu; Abram L. Wagner; Kuldeep Dhama (School of Medicine, Universitas Syiah Kuala, 2021)
In Indonesia, the most populous Moslem-majority country, despite the possibility of underreported coronavirus disease (COVID-19) cases, 6,248 confirmed cases and 535 deaths have been recorded. With upcoming Ramadan and Eid al-Fitr, between 18-23 million of Indonesians may move from urban locations (with high counts of COVDI-19) to rural areas with fewer cases currently but less laboratory capacity to diagnose cases. This review summaries the current situation of CO.VID-19 in Indonesia and discusses the possible impacts of mass population movement, Ramadan-related activities, and Eid al-Fitr celebration days on COVID-19 transmission in the country.